LITERASI KESEHATAN MENTAL PADA REMAJA SEBAGAI UPAYA PREVENTIF MENGATASI MASALAH KESEHATAN MENTAL DI KOTA TERNATE - Amalia S.J Kahar; Husnul Hasanah N. Saleh (Universitas Muhammadiyah Gresik, 2025)
Background: Adolescent mental health is a concern because there is an increase in mental problems to suicidal behavior among adolescents. Mental health literacy is one way for adolescents to reduce the negative impact of mental problems that arise. Objective: This study aims to determine the effectiveness of psychoeducation to improve adolescent mental health literacy as a preventive effort to overcome mental health problems in Ternate City. Method: This research method uses a true experimental design research type in the form of a pretest posttest control group design. The respondents obtained in this study were 48 high school students aged 15-18 years. The research instrument used the Mental Health Literacy Scale (MHLS) developed by (O’Connor & Casey, 2015). Data were analyzed using Anova mix design using SPSS. Result: he results showed differences in mental health literacy between the experimental group and the control group. The Experimental Group had a higher mental health literacy score than the experimental group after being given the intervention. The F value was obtained at 29.435 and a significance level of 0.000 (p <0.01). Conclusion: So it can be concluded that psychoeducational interventions are able to improve adolescent mental health literacy and can be used as a preventive effort to reduce mental health problems in Ternate.